Efficiencies of platform clinical trials: A vision of the future. (June 2016) - Saville, Benjamin R; Berry, Scott M
Background: A "platform trial" is a clinical trial with a single master protocol in which multiple treatments are evaluated simultaneously. Adaptive platform designs offer flexible features such as dropping treatments for futility, declaring one or more treatments superior, or adding new treatments to be tested during the course of a trial. Methods: A simulation study explores the efficiencies of various platform trial designs relative to a traditional two-arm strategy. Results: Platform trials can find beneficial treatments with fewer patients, fewer patient failures, less time, and with greater probability of success than a traditional two-arm strategy. Conclusion: In an era of personalized medicine, platform trials provide the innovation needed to efficiently evaluate modern treatments.